Auxin and gibberellin responsive Arabidopsis SMALL AUXIN UP RNA36 regulates hypocotyl elongation in the light - Stamm, Petra; Kumar, Prakash P (Plant cell reports, 2013)
KEY MESSAGE : The Arabidopsis SAUR36 , renamed RAG1 , integrates auxin and gibberellin signals to regulate apical hook maintenance in etiolated seedlings, hypocotyl elongation in the light and fertility. Phytohormone signalling intermediates integrate responses to developmental cues and the variety of environmental inputs thereby governing all aspects of plant growth and development. At the genetic level, interactions of different phytohormone signalling pathways lead to the regulation of overlapping sets of target genes. We have characterised SMALL AUXIN UP RNA 36 (SAUR36, At2g45210) whose expression is induced by auxins and repressed by gibberellins. Its expression appears to be restricted to elongating tissues. Germination responses to treatments with paclobutrazol and exogenous abscisic acid were affected in knock-out, knock-down as well as ectopic expression lines. At later stages of development, however, transgenic plants with reduced levels of SAUR36 expression appeared similar to wild-type plants, while ectopic expression of SAUR36 led to the absence of apical hooks in etiolated seedlings and longer hypocotyls in light-grown seedlings. Mature plants ectopically expressing SAUR36 further displayed strongly reduced fertility and wavy growth of inflorescence axes, the latter of which could be linked to defects in auxin transport. Taken together, our data suggest that SAUR36 plays a role in the regulation of seed germination by gibberellins and abscisic acid, light-dependent hypocotyl elongation as well as apical hook formation or maintenance. Therefore, we propose that it could act as one of the converging points of auxin and gibberellin signal integration in controlling key plant developmental events. Hence, we named the gene RESPONSE TO AUXINS AND GIBBERELLINS 1 (RAG1).